2018
DOI: 10.3389/fphys.2018.01501
|View full text |Cite
|
Sign up to set email alerts
|

Compound Danshen Dripping Pill Inhibits Retina Cell Apoptosis in Diabetic Rats

Abstract: Scope: Diabetic retinopathy (DR) is a severe microvascular complication of diabetes. Previous clinical trials have shown that Compound Danshen Dripping Pill (CDDP) improves DR symptoms. However, the mechanism involved remains unclear.Procedures: Rats fed a high-fat diet and injected with streptozotocin (STZ) were used as an experimental type 2 diabetes rodent model. CDDP was administered to two groups of diabetic rats at 0.2 and 0.4 g/kg/day via gastric gavage for 12 weeks. After the 12 weeks of treatment, ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…SD rats are also sensitive to HFD feeding in combination with only one STZ injection of the same dosage (30 mg/kg). In fact, after 16 weeks of treatment, diabetic SD rats presented some features of early stages of DR, such as abnormal b-waves and OPs, and diabetic rats had lower total retina and outer nuclear layer (ONL) thickness compared to control rats [63].…”
Section: Diet-induced Models Of Diabetic Retinopathymentioning
confidence: 99%
“…SD rats are also sensitive to HFD feeding in combination with only one STZ injection of the same dosage (30 mg/kg). In fact, after 16 weeks of treatment, diabetic SD rats presented some features of early stages of DR, such as abnormal b-waves and OPs, and diabetic rats had lower total retina and outer nuclear layer (ONL) thickness compared to control rats [63].…”
Section: Diet-induced Models Of Diabetic Retinopathymentioning
confidence: 99%
“…Furthermore, CDDP showed a potential in uence on CASP-3, a downstream executioner of apoptosis in DR, [57][58][59][60] in our study and its inhibitory effect on CASP-3 expression has been reported. 61 Combining with the GO enrichment analysis, CDDP was strongly indicated involved in the regulation of steroid hormone response and apoptosis in DR.…”
Section: Discussionmentioning
confidence: 97%
“…In an in vitro model of hypoxia and reoxygenation, Hu's [10] study showed that Radix salviae obviously alleviated cardiomyocyte apoptosis and protected mitochondrial function and cell membrane skeleton integrity in H9c2 cells. In addition, Zhang's experiment in rodents [11] revealed that Danshen (Radix salviae) dripping pill inhibited apoptosis and exerted neuroprotective effects in the retinas of diabetic rats by increasing the expression of Bcl-2, Bcl-2 associated X and caspase-3 in diabetic rats. Moreover, according to the I-T networks of CXC and HXMMT, Radix salviae contained a greater number of active ingredients related to potential therapeutic targets in PDR than did the other herbal components, suggesting that Radix salviae may play a crucial role in PDR treatment.…”
Section: Discussionmentioning
confidence: 99%